Irbesartan treatment does not influence plasma levels of the dicarbonyls methylglyoxal, glyoxal and 3‐deoxyglucosone in participants with type 2 diabetes and microalbuminuria: An IRMA2 sub‐study. Issue 9 (16th October 2020) - Piazza, M.; Hanssen, N. M. J.; Persson, F.; Scheijen, J. L.; van de Waarenburg, M. P. H.; van Greevenbroek, M. M. J.; Rossing, P.; Hovind, P.; Stehouwer, C. D. A.; Parving, H‐H.; Schalkwijk, C. G.
Abstract: Aim: Angiotensin receptor blockers (ARBs) reduce vascular complications in diabetes independently of blood pressure. Experimental studies suggested that ARBs may restore the detoxifying enzyme glyoxalase 1, thereby lowering dicarbonyls such as methylglyoxal. Human data on the effects of ARBs on plasma dicarbonyl levels are lacking. We investigated, in individuals with type 2 diabetes, whether irbesartan lowered plasma levels of the dicarbonyls methylglyoxal, glyoxal, 3‐deoxyglucosone and their derived advanced glycation end products (AGEs), and increased d ‐lactate, reflecting greater methylglyoxal flux. Methods: We analysed a subset of the Irbesartan in Patients with T2D and Microalbuminuria (IRMA2) study. We measured plasma dicarbonyls methylglyoxal, glyoxal and 3‐deoxyglucosone, free AGEs and d ‐lactate using ultra‐performance liquid chromatography tandem mass‐spectrometry (UPLC‐MS/MS) in the treatment arm receiving 300 mg irbesartan ( n = 121) and a placebo group ( n = 101) at baseline and after 1 and 2 years. Effect of treatment was analysed with repeated measurements ANOVA. Results: There was a slight, but significant difference in baseline median methylglyoxal levels [placebo 1119 (907–1509) nmol/l vs. irbesartan 300 mg 1053 (820–1427) nmol/l], but no significant changes were observed in any of the plasma dicarbonyls over time in either group and there was no effect of irbesartan treatment on plasma free AGEs or d ‐lactate levels at either 1 or 2 years. Conclusion: Irbesartan treatment does not change plasma levels of the dicarbonyls methylglyoxal, glyoxal and 3‐deoxyglucosone, free AGEs or d ‐lactate in type 2 diabetes. This indicates that increased dicarbonyls in type 2 diabetes are not targetable by ARBs, and other approaches to lower systemic dicarbonyls are needed in type 2 diabetes. (Clinical Trial Registry No: #NCT00317915).